Broadband X-Ray Timing and Spectral Characteristics of the Accretion-powered Millisecond X-Ray Pulsar MAXIJ1816-195 - Li Zhaosheng; Kuiper Lucien; Ge Mingyu; Falanga Maurizio; Poutanen Juri; Ji Long; Pan Yuanyue; Huang Yue; Xu Renxin; Song Liming; Qu Jinlu; Zhang Shu; et al. (Institute of Physics Publishing, 2025)
We studied the broadband X-ray timing and spectral behaviors of the newly confirmed accreting millisecond X-ray pulsar MAXI J1816−195 during its 2022 outburst. We used data from the Insight-HXMT Medium Energy (ME) and High Energy (HE) telescopes, NICER, and NuSTAR that cover the energy range between 0.8 and 210 keV. A coherent timing analysis of solely the Insight-HXMT HE data across the full outburst revealed a complex behavior of the timing residuals, also prominently visible in the independent Insight-HXMT ME and NICER data, particularly at the rising part of the outburst and at the very end in the NICER data. Therefore, we broke down the full outburst into a (noisy) rising part, covering only about five days, from MJD 59737.0 to 59741.9, and a decaying part, lasting for 19 days across MJD 59741.9–59760.6. Fitting for the decaying part, a timing model including a frequency ν and frequency time derivative component yielded a value of (+9.0 ± 2.1) × 10−14 Hz s−1 for , which could be interpreted as a spinup under our model assumptions. We detected X-ray pulsations up to ∼95 keV in a combination of Insight-HXMT HE observations. The pulse profiles were quite stable over the whole outburst and could be well described by a truncated Fourier series using two harmonics, the fundamental and the first overtone. Both components kept alignment in the range 0.8–64 keV. The joint and time-averaged NICER and Insight-HXMT spectra in the energy range 1–150 keV were well fitted by the absorbed Comptonization model compps plus disk blackbody with two additional Gaussian components. Using the bolometric flux and spinup values both evaluated during the decay phase, we determined a magnetic field strength of (0.2–2) × 108 G for MAXI J1816−195.